Factors Related to Health Worker Compliance in Implementing Infection Prevention and Control in Hospitals - Amiruddin Amiruddin; Sumijatun Sumijatun; Ali Germas Kodyat (Indonesian Journal of Global Health Research, 2025)
Based on a 2019 report, Bhayangkara Hospital Level III Banda Aceh had an HAI or nosocomial infection incidence rate of 1.97%. There were no other cases of infection. In 2020, out of 91 healthcare workers, only 5 (5.49%) had received training on how to prevent and control infections. The purpose of this study was to determine factors related to healthcare worker compliance in implementing infection prevention and control at Bhayangkara Hospital Level III Banda Aceh. Quantitative research was used with a cross-sectional study design. A sample of 91 healthcare workers was selected using a total sampling method. Data collection used an instrument created by the researcher from available literature. Data were analyzed descriptively and inferentially. The results showed a partial significant relationship between knowledge (p = 0.004), attitude (p = 0.016), and experience (p = 0.0001) with compliance in infection prevention and control at Bhayangkara Hospital Level III Banda Aceh. Logistic regression analysis showed that knowledge (P = 0.002) and experience (P = 0.0001) were significant predictors related to compliance with infection prevention and control at Bhayangkara Hospital Level III Banda Aceh. The conclusion of the study was that experience was the most significant predictor related to compliance with infection prevention and control at Bhayangkara Hospital Level III Banda Aceh (OR: 14.327).